PENGUATAN MODERASI BERAGAMA MELALUI PENDIDIKAN ISLAM NONFORMAL: STUDI KASUS MAJLIS TAKLIM SYECH MUHYIDDIN, GRESIK - muzakki abdurrahman (Institut Agama Islam Sahid (INAIS) Bogor, 2026)
This study aims to describe how the majlis taklim contributes to strengthening religious moderation at Majlis Taklim Syech Muhyiddin, Kedung Rukem, Benjeng, Gresik. The inquiry focuses on forms of guidance, religious teaching materials, socio-religious practices of congregants, and organizational strategies for instilling the values of religious moderation. A descriptive qualitative approach was employed through participant observation, in-depth interviews with administrators, religious instructors (ustaz/ustazah), and congregants, as well as a review of internal documents. Data were analyzed using the stages of data reduction, data display, and conclusion drawing/verification, accompanied by source and method triangulation. The findings indicate four main points: (1) a thematic learning design emphasizing tolerance, balance, and non-violence; (2) role modeling by instructors and administrators that reflects inclusive religious practice; (3) the integration of local wisdom through socio-cultural activities that strengthen community cohesion; and (4) consistent program governance comprising a simple curriculum, a congregational code of conduct, and inter-neighborhood (RT/RW) collaboration. These results show that the majlis taklim functions effectively as a non-formal educational space that fosters religious moderation at the levels of discourse, attitude, and behavior. The study recommends strengthening the moderation curriculum, facilitator training, and partnerships with local religious institutions.